English Teaching in Elementary School: Parents’ Expectation and Reality - Agustinus Ngadiman; Davy Budiono (Widya Mandala Surabaya Catholic University, 2009)
The need for the teaching of English as a foreign language in Indonesia has been felt by almost all levels of society, especially in big cities. Without realizing the schools readiness, society has put a great expectation on the success of the English teaching. Theories on Second Language Acquisition suggest that a foreign language should be taught to children of young age because every individual possesses a language Acquisition Device, regardless of the age (Chomsky, 1962). Lanneberg (Krashen, 1988: 72) claimed that children are biologically capable to learn a language easily due to the elasticity nature of their brain. This elasticity will stop once the lateralization process takes place in a time when children usually begin to enter their puberty period. In accordance to the 1994 National Curriculum, English has been formally introduced to students of Elementary School. Now, at the dawn of the implementation of competence Based Curriculum, elementary schools are reformulating their English syllabuses and materials to respond to parents’ expectations. This paper intends to describe these expectations along with what the schools have done to respond these expectations based on a survey conducted on a number of elementary schools in Surabaya. Furthermore, the paper will also try to verify whether these expectations are realistic or not and suggest several achievement indicators that are in line with these realistic expectations.